Product Market Competition and the Severity of Distressed Asset Sales - Salgado, Pablo; Carrasco, Vinicius; De Mello, João Manoel Pinho (Review of Finance, 2017)
This article explores the effect of an industry’s market structure on the liquidation value of assets. We show that when firms with financial constraints compete for the gains arising from market concentration, they expend insufficient efforts to deploy assets across industries, leading to significant liquidation discounts when compared with an efficient benchmark. Equilibrium distress costs and private costs of leverage should increase with the rents linked to concentration in the product market.